Musical echoes of a trauma: Listening to phantasms in the dark fantasy Pan’s Labyrinth (2006) - Buljančević Rastko (Muzikologija)
This article examines how music in the film Pan’s Labyrinth [El laberinto del fauno] conceptually generates opposing phantasms. Reflecting the trauma of early Francoism, specifically the Spanish Civil War, the soundtrack oscillates between the disquieting chronological reality and the fascinating yet terrifying fairytale world. A special space is devoted to the musical redistribution of the sensible, mirroring the strong affective, aesthetic, emancipatory, and phantasmatic potential of Foley sounds. Such musical resistance undermines phallic authority, fostering a phantasmatic conflict that blurs the boundaries between imaginable and unimaginable reality.